GENESIS OF THE CONCEPT OF INNOVATION AND ITS ANALYSIS - Nosir Juraboev (Research Parks Publishing LLC, 2021)
This article analyzes the changes in the world education system, the national education system, the interrelationship of education with innovation, development, the genesis of the concept of innovation and its current state. method, such as the social mechanism of innovation development